2020
DOI: 10.3390/agronomy10060826
|View full text |Cite
|
Sign up to set email alerts
|

Legume-Rhizobium Strain Specificity Enhances Nutrition and Nitrogen Fixation in Faba Bean (Vicia faba L.)

Abstract: This study reports the effectiveness of some selected rhizobium strains in enhancing nitrogen fixation and nutrient uptake in Vicia faba L. Multi-location field experiments were conducted for two years (2016 and 2017) using a split-plot in randomized complete block design. Treatments comprised six rhizobium strains as the main plot factor and three varieties of Vicia faba as the sub-plot factor. Non-inoculated plants with or without N fertilizer served as +N and −N controls, respectively. Peat carrier-based in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 68 publications
2
19
0
Order By: Relevance
“…Cover crops are necessary to maintain the richness of rhizobacteria, which intervene in the assimilation of nutrients and in plant growth [53,54]. The cover crop acts as a protective element of the soils, which reduces evapotranspiration, minimizing crop irrigation [55,56], and not being necessary the breakages that destroy the soil mycorrhizae that allow the nitrogen entry into nodular systems [57][58][59][60][61]. Nitrogen fixation by mycorrhizal fungi is essential for sustainable cultivation to be productive [62][63][64]: for this, it is essential to know certain edaphic parameters, since within the Fabaceae family, there are species indifferent edaphic to pH, being able to be acidophilic exclusively or basophilic.…”
Section: Discussionmentioning
confidence: 99%
“…Cover crops are necessary to maintain the richness of rhizobacteria, which intervene in the assimilation of nutrients and in plant growth [53,54]. The cover crop acts as a protective element of the soils, which reduces evapotranspiration, minimizing crop irrigation [55,56], and not being necessary the breakages that destroy the soil mycorrhizae that allow the nitrogen entry into nodular systems [57][58][59][60][61]. Nitrogen fixation by mycorrhizal fungi is essential for sustainable cultivation to be productive [62][63][64]: for this, it is essential to know certain edaphic parameters, since within the Fabaceae family, there are species indifferent edaphic to pH, being able to be acidophilic exclusively or basophilic.…”
Section: Discussionmentioning
confidence: 99%
“…Makoi et al (2013) reported that rhizobial inoculation significantly improved the uptake of nutrients such as P, K, Ca, and Mg in different plant parts such as leaves, shoots, roots, and pods of common beans (Phaseolus vulgaris L.). Allito et al (2020) indicated that inoculation of faba bean with diverse rhizobial strain caused a significant improvement in nitrogen uptakes which ranged from 194.7 to 309.6 kg N ha −1 as compared to the un-inoculated control as well as soil nitrogen balance is also increased following inoculation of rhizobia. These authors indicated that the increment in the nitrogen uptake and soil nitrogen balance is mainly accredited to improved nitrogen fixation.…”
Section: Rhizobial Inoculation Improves Nutrient Availability and Uptake By Plantsmentioning
confidence: 99%
“…Moreover, Kong Z. et al (2015) , Kong Z. Y. et al (2015) , and Chen et al (2018) reported that alfalfa-rhizobium symbiosis can promote plant growth and regulate antioxidant enzyme activity through the synthesis of indoleacetic acid and iron carriers. Allito et al (2020 , 2021) studied the effect of legume-rhizobium symbiosis on the biomass, nodulation, nitrogen fixation and nutrient uptake efficiency of faba bean. However, the soil-plant system is a whole, and the detailed mechanism of legume-rhizobium mediated mitigation of Cu-stress via the biochemical response of the plant-soil system is still limited.…”
Section: Introductionmentioning
confidence: 99%